Electronic imaging in astronomy detectors and instrumentation - McLean, Ian S. (Springer praxis books, 2008)
The second edition of Electronic Imaging in Astronomy: Detectors and Instrumentation describes the remarkable developments that have taken place in astronomical detectors and instrumentation in recent years – from the invention of the charge-coupled device (CCD) in 1970 to the current era of very large telescopes, such as the Keck 10-meter telescopes in Hawaii with their laser guide-star adaptive optics which rival the image quality of the Hubble Space Telescope. Authored by one of the world’s foremost experts on the design and development of electronic imaging systems for astronomy, this book has been written on several levels to appeal to a broad readership. Mathematical expositions are designed to encourage a wider audience, especially among the growing community of amateur astronomers with small telescopes with CCD cameras. The book can be used at the college level for an introductory course on modern astronomical detectors and instruments, and as a supplement for a practical or laboratory class. The development of electronic imaging in astronomy - Beating the atmosphere - Telescopes - The discovery power of modern astronomical instruments - Instrumentation and detectors - Designing and building astronomical instruments - Charge-coupled devices - Practical operation of CCDs - Characterization and calibration of array instruments - Image processing and analysis - Electronic imaging at infrared wavelengths - Electronic imaging at ultraviolet, X-ray, and gamma-ray wavelengths - Electronic imaging at sub-millimeter and radio wavelengths - Future developments.